Molecular genetic analysis of cytosine-adenine-guanine repeats in huntingtin gene - Gadhia, Pankaj; Sangani, Avani; Vaniawala, Salil (Eastern Journal of Medical Sciences, 2024)
Background: Huntington’s disease (HD) is a dominantly transmitted progressive neurodegenerative disorder due to abnormal expansion of cytosine-adenine-guanine (CAG) repeats in the huntingtin gene. Materials and Methods: The study involved a total of 35 HD patients identified through clinical evaluations. CAG repeats expansion analysis was conducted using polymerase chain reaction (PCR) to confirm positive cases. Results: Employing CAG flacking PCR in 35 cases, 19 tested positive, predominantly displaying CAG repeats in the range of 40–50. Noteworthy cases include a 5-month-old patient with 44 CAG repeats and an 80-year-old patient with 46 CAG repeats. Conclusion: The identification of the genetic defect in HD permits direct genetic testing to comprehend the complexities of HD in India, aiming for effective approaches in diagnosis, treatment, and prevention.